Aktivitas sitotoksik dan antiangiogenesis umbi mentimun papasan (Coccinia grandis L.Voight) terhadap sel kanker hela yang diinduksi protein bFGF - Djamal, Julia Megawati; P, Jason Merari; Rukmana, Rizal Maarif (Riset Informasi Kesehatan, 2020)
Background : Cancer is a leading cause of death in Indonesia and in the world. Cervical cancer is one of the most common cancers in women. One of the plants that has the potential to be developed as an alternative treatment for cancer is the papasan cucumber tuber (Coccinia grandis (L) Voight). This study aims to determine the activity of cytotoxic effects on Hela cancer cells and antiangiogenesis activity against Chorioallantoic membrane. Method : In this study, papasan cucumber tubers were extracted with 96% ethanol solvent. The ethanol extract was then continued with fractionation using the liquid-liquid partition method, followed by thin-layer chromatography used to determine of compounds contained in the papasan cucumber tubers. Cytotoxic activity tests were carried out using the MTT assay method and antiangiogenesis tests were carried out using CAM methods of chicken embryos induced with bFGF protein. Results : The results showed that the extract, n-hexane fraction, ethyl acetate fraction and water fraction had IC 50 values 986,604 µg/ml, 208,776 µg/ml, 187,824 µg/ml and 553,393 µg/ml. The IC 50 value of the n-hexane fraction was then continued with antiangiogenesis testing. The KLT analysis showed that the n-hexane fraction contained alkaloids, flavonoids, tannins, saponins, and terpenes. Antiangiogenesis test result show that the inhibitory at concentration of 104 µg / ml was 17,56%, at a concentration of 208 µg / ml 43,23% and at a concentration of 418 µg / ml 56,78%. Conclusion : n-hexane fraction and ethyl acetate fraction have moderate cytotoxic activity against Hela cancer cells and n-hexane fraction has antiangiogenesis activity. Key words: Coccnia grandis L. Voight, Cytotoxic, Antiangiogenesis, Hela, Chorioallantoic Membrane